The IMF and the future : issues and options facing the fund - Bird, Graham; International Monetary Fund (London ; New York : Routledge, 2003)
Starting with a historical background tracing the evolution of the IMF, the book goes on to cover such themes as: the circumstances under which countries turn to the IMF, the various aspects of IMF conditionality, institutional issues such as lending facilities and how the Fund is resourced, and the political economy of IMF issues." "The book will undoubtedly be required reading for anyone with a serious interest in development studies, international relations and international economic policy.
Includes bibliographical references and index.
aia 12/8/16
Loans
Keywords: International finance; International Monetary Fund -- Developing countries